Cervical opening during estrus in Aceh Local Cows based on camera-equipped artificial insemination endoscope - Komala Ulfa; Hendra Saputra; Tazul Arifin; Cut Nila Thasmi; Hafizuddin; Etriwati; Abdullah Hamzah (Ovozoa: Journal of Animal Reproduction, 2023)
Twelve healthy and not pregnant local cows, aged 3-6 years, 1-3 parity. The cows were synchronized using the PGF2α of 5 ml/cow intramuscularly, twice at 11 days intervals. The Estrus detection based on the scoring of van Eerdenburg was conducted 24 hours after the second prostaglandin injection three times daily for three days. The changes in cervical dilatation were observed at 0, 6, and 12 hours from the onset of estrus. The result showed that 8 of 12 cows were estrus after twice PGF2α injection. All the estrus cows showed mild cervical dilatation with liquid and transparent mucus (opening cervix score 1) at 0-hour observation. Six hours later, 62.50% of cows remained at opening cervix score 1, and 37.50% changed to opening cervix score 2 (optimum cervical dilatation with thick and transparent mucus). At 12 hours after the onset of estrus, 25% of estrus cows had cervical closure (opening cervix score 0, closed cervical with thick and turbid mucus), and 75% changed to opening cervix score 2. In this study, 75% of the cows experienced an optimum open cervix at 12 hours from the onset of estrus. It could be concluded that opening the external cervical canal of local Aceh cows reaches optimum at 12 hours from the onset of estrus.